2013
DOI: 10.18552/joaw.v3i1.96
|View full text |Cite
|
Sign up to set email alerts
|

From Apprenticeship Genres to Academic Literacy: Problematising Students’ and Teachers’ Perceptions of Communication Activities in an ICL Environment

Abstract: Comparatively little research has been done on students' perceptions of communication and communication activities in integrated content and language (ICL) environments. In the present study, student statements about communication and communication activities have been collected via interviews and surveys from students attending a mechanical engineering programme in Sweden. These statements are compared with statements from content teachers at the same programme. Results suggest that students and teachers shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…According to Aguilar (2017), Spanish engineering lecturers preferred EMI over CLIL as they did not want to teach language. Eriksson and Carlsson (2013) showed that both groups of mechanical engineering students and teachers at a Swedish university believed that communication activities should include apprenticeship genres that students could use in their future careers. Aguilar and Rodr ıguez (2012) report that most of the engineering students studying at a Spanish university felt positive about their CLIL experience, but they were critical of lecturers' insufficient levels of English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Aguilar (2017), Spanish engineering lecturers preferred EMI over CLIL as they did not want to teach language. Eriksson and Carlsson (2013) showed that both groups of mechanical engineering students and teachers at a Swedish university believed that communication activities should include apprenticeship genres that students could use in their future careers. Aguilar and Rodr ıguez (2012) report that most of the engineering students studying at a Spanish university felt positive about their CLIL experience, but they were critical of lecturers' insufficient levels of English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the B2 descriptors include "conventions of formal correspondence", and the questionnaire has shown that more than half of the students declared they write e-mails in study/ work situations in English, and mentioned e-mails, together with the CV, as the genres they would like to focus on in a future course on writing or ESP. Overall, given the importance of genres that emerged from the questionnaire, we think that genre awareness should be raised to help students develop literacy in apprenticeship genres, as in Eriksson & Carlsson (2013), i.e., the notion that genre writing might have a role in the socialization into a discipline, its activities and the contexts associated with them, such as the lab.…”
Section: Discussionmentioning
confidence: 99%
“…Students in one of the two departments in this study face a common challenge (Eriksson and Carlsson 2013) of combining communication skills with subject skills. If they are used to writing short technical reports, the requirements to write about theory and other sections in a thesis can be overwhelming for the individual student.…”
Section: Writing a Thesis Is A Complex Taskmentioning
confidence: 99%